Availability of pearl producing marine bivalves in south-eastern coast of Bangladesh and culture potentialities - Rahman, Md. Ataur; Parvej, Mohammed Rashed; Rashid, Md. Harunor; Hoq, Md. Enamul (Journal of Fisheries, 2015)
The present study was conducted during September 2014 to July 2015 to identify the pearl bearing bivalves in south-eastern coast of Bangladesh and culture potentialities of marine oyster in captivity based on field investigation. A total of 7 pearl bearing bivalve species were identified in the coast with a salinity of 18-34 ppt, pH 8.1-8.3 and water depth ranged 0.2-2.0 meter in their habitat. From the collected bivalves, most abundant oyster species windowpane oyster, Placuna placenta (Linnaeus, 1758) was reared in fiber glass tanks with seawater for a period of 6 months. During rearing highest survival rate of 88% was observed in T1 with sandy and gravel substratum and lowest survival rate of 78% was found in T2 with muddy substratum. Average temperature and salinity were varied between 24 °C-25 °C and 21-26 ppt respectively. From the reared oyster, highest 54 nos. small pearls in the month of April and lowest 7 pearls in December from a single P. placenta were obtained. The study proved that pearls can be obtained from the marine oysters in captivity in Bangladesh, and this offers large scale culture potentialities in our coast.